Physiological determinants of three-kilometer running performance in experienced triathlete - Slattery, K. M.; Wallace, L. K.; Murphy, A. J.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2006)
The present investigation examined the physiological parameters that contribute to 3-km running performance. Following 2 familiarization sessions, 16 experienced male triathletes (O2max = 55.7 ± 4.9 ml·kg-1·min-1, age = 31.3 ± 11.7 years) performed a 3-km time trial (3kmTT) and were assessed for selected physiological and anthropometrical characteristics. Stepwise multiple regression and correlation analysis was used to determine the variables that significantly related to 3kmTT. The analysis revealed that 82.3% of the adjusted variance in 3kmTT performance could be explained by peak treadmill running velocity during a O2max test (Vmax) alone. The addition of the running velocity at lactate threshold (LTvel) and peak lactate concentration ([BLa-]peak) to the prediction equation allowed for 93.6% of the adjusted variance in 3kmTT to be predicted (Y = -13.64 Vmax - 25.61 LTvel - 5.40 [BLa-]peak + 1358.5). Correlation analysis revealed that Vmax (r = -0.91), LTvel (r = -0.90), and O2max (r = -0.80) were significantly related to running performance. These results show that Vmax was the single best predictor of 3-km running performance in experienced male triathletes and that both aerobic and anaerobic abilities are related to improved 3kmTT performance. Since the assessment of Vmax is relatively simple to implement, we suggest that determining Vmax may be a practical method for monitoring performance changes in short-term endurance running events.